2021
DOI: 10.3390/geriatrics6040099
|View full text |Cite
|
Sign up to set email alerts
|

Aromatherapy Massage vs. Foot Reflexology on the Severity of Restless Legs Syndrome in Female Patients Undergoing Hemodialysis

Abstract: This study aimed to compare the effects of reflexology and aromatherapy massage on the severity of restless legs syndrome (RLS) in 105 female patients undergoing hemodialysis. A randomized placebo-controlled clinical trial was conducted in a hemodialysis center with 48 beds in a high turnover hospital in an urban area of Iran. Intervention groups received reflexology (n = 35) and aromatherapy massage using lavender essential oil (n = 35) for 24 sessions, and the placebo group (n = 35) received simple foot mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…For example, Ajorpaz et al claimed that massage with glycerin oil and lavender oil could effectively reduce RLS in hemodialysis patients [ 31 ]. Similarly, Ghasemi et al showed that the use of aromatherapy foot massage was effective in the reduction of RLS symptoms in women undergoing hemodialysis [ 32 ]. Although the mechanism and causes of RLS are different in CCNs and hemodialysis patients, it should be borne in mind that complementary medicine interventions (e.g., local heat therapy or massage without or with aromatherapy) cause a sense of comfort and relaxation in the RLS-affected organ, eventually reducing the symptoms of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ajorpaz et al claimed that massage with glycerin oil and lavender oil could effectively reduce RLS in hemodialysis patients [ 31 ]. Similarly, Ghasemi et al showed that the use of aromatherapy foot massage was effective in the reduction of RLS symptoms in women undergoing hemodialysis [ 32 ]. Although the mechanism and causes of RLS are different in CCNs and hemodialysis patients, it should be borne in mind that complementary medicine interventions (e.g., local heat therapy or massage without or with aromatherapy) cause a sense of comfort and relaxation in the RLS-affected organ, eventually reducing the symptoms of this syndrome.…”
Section: Discussionmentioning
confidence: 99%